Carbon paper for metal modified fuel cell and manufacturing method of carbon paper

By adding titanium hydride powder to the carbon paper precursor and performing gas hot pressing treatment, combined with carbonization and graphitization of alcohol-soluble thermosetting resin, the problem of carbon paper reducing strength during graphitization is solved, and conductivity and breathability are achieved Improved performance and reduced production costs.

CN119287698APending Publication Date: 2025-01-10BEIJING MECHANICAL EQUIP INST
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411160187.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The strength of existing carbon paper is reduced during graphitization, making it difficult to meet the mechanical strength and conductivity requirements of fuel cells. At the same time, high-temperature treatment increases energy consumption and production costs.

Method used

By immersing the carbon paper precursor in the impregnation liquid of titanium hydride powder and performing gas hot pressing treatment, the titanium hydride is decomposed into titanium and hydrogen to form a microporous structure, and carbonization and graphitization are carried out in combination with an alcohol-soluble thermosetting resin, and React with carbon fiber at high temperatures to improve conductivity and bonding force, and use nickel plating to improve mechanical properties.

Benefits of technology

It has achieved improvements in conductivity and breathability, reduced the resistivity and production energy consumption of carbon paper, and improved the mechanical strength of carbon paper and the feasibility of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287698A_ABST
    Figure CN119287698A_ABST
Patent Text Reader

Abstract

The invention discloses carbon paper for a metal modified fuel cell and a manufacturing method of the carbon paper. The manufacturing method comprises the following steps: 1) dipping a carbon paper precursor in a dipping solution added with titanium hydride powder; (2) drying the impregnated carbon paper precursor; 3) clamping the dried carbon paper precursor in the middle of a graphite plate and putting the graphite plate into a sintering furnace for gas hot pressing; (4) releasing furnace chamber gas after gas hot pressing is finished, and heating the sintering furnace to a preset temperature at a preset heating speed in a positive pressure environment; and 5) performing carbonization and graphitization treatment in a sintering furnace in sequence after the step 4). According to the invention, the carbon paper precursor is impregnated and doped with titanium hydride powder and is subjected to hot-pressing treatment, so that titanium hydride is decomposed into metal titanium and hydrogen, escape of hydrogen can form micropores in the resin wrapping the hydride powder, the air permeability of the carbon paper is improved, the metal titanium can chemically react with carbon element at high temperature to generate carbide, and the carbon paper has good air permeability. The binding force with the carbon fiber is improved; and the conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of processing key supporting materials for fuel cells, and in particular to carbon paper for metal-modified fuel cells and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a device that directly converts chemical energy into electrical energy. It has outstanding characteristics such as high energy density and current density, low operating temperature, etc. It has huge market potential in the fields of new energy vehicles, military spacecraft, submarine power supplies, etc.

[0003] The basic unit of PEMFC consists of a proton exchange membrane, a catalyst layer, a gas diffusion layer (GDL) and a bipolar plate. The GDL consists of a substrate layer and a microporous layer. The substrate is generally made of carbon paper, carbon fiber woven cloth, carbon felt, carbon black paper and other sheets. Carbon paper has become one of the main materials for preparing GDL due to its light weight, smooth surface, corrosion resistance, uniform pores, high strength and mature manufacturing process. Carbon paper plays the role of transporting reaction gases, discharging product water, supporting the catalyst layer, collecting current, etc., and realizing the redistribution of product water and reaction gases. It is one of the key components affecting electrode performance. Carbon paper needs to have the following properties: (1) Certain strength. It needs to have high mechanical strength and appropriate softness to provide structural support for the fuel cell. (2) Appropriate pore size structure. It is used for gas transport during the operation of the fuel cell and the discharge of water after the electrochemical reaction to ensure the smooth progress of the electrochemical reaction. (3) Low resistivity. It is conducive to the electron transmission in the carbon paper, reduces the contact resistance between the carbon paper and other components, and ensures the output power of the fuel cell. (4) Appropriate thickness and apparent density. Improve the ability of carbon paper to transmit gas and moisture.

[0004] At present, there are many patents related to the preparation of carbon paper. For example, patents CN100336972C and CN1331261C use carbon fiber and adhesive to make base paper, and then make carbon paper through thermosetting resin impregnation, hot pressing and graphitization. The carbon material can be transformed from a disordered chaotic layer structure to graphitization through high-temperature heat treatment at 2200℃-2800℃. The higher the temperature and the longer the insulation time, the higher the degree of graphitization. However, as the graphitization temperature increases, the carbon paper itself gradually becomes brittle and the tensile strength decreases, which brings serious problems to its mass preparation and application. And because the resin is hard carbon, it is difficult to achieve a low resistivity even with ultra-high temperature treatment, which also increases energy consumption and production costs. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a metal-modified carbon paper for fuel cells having good electrical conductivity, air permeability and high mechanical strength and a method for manufacturing the same.

[0006] To achieve the above object, the present invention provides a method for manufacturing metal-modified carbon paper for fuel cells in a first aspect, comprising the following steps:

[0007] 1) impregnating a carbon paper precursor in an impregnation solution containing titanium hydride powder;

[0008] 2) drying the impregnated carbon paper precursor;

[0009] 3) The dried carbon paper precursor is clamped between the graphite sheets and placed in a sintering furnace for gas hot pressing;

[0010] 4) After the gas hot pressing is completed, the furnace chamber gas is released, and the sintering furnace is heated to a predetermined temperature at a predetermined heating rate under a positive pressure environment, so that the titanium hydride is completely decomposed into titanium and hydrogen;

[0011] 5) After step 4), carbonization and graphitization are sequentially performed in a sintering furnace.

[0012] Further, step 5) further includes the following steps:

[0013] 6) The graphitized sample after step 5) is subjected to nickel plating to obtain metal-modified carbon paper for fuel cells.

[0014] Furthermore, in step 1), the amount of titanium hydride powder added is 1 to 10 wt. % of the mass of the impregnation solution.

[0015] Furthermore, the impregnation liquid includes 50-75% of anhydrous ethanol and 25-50% of alcohol-soluble thermosetting resin in terms of weight percentage.

[0016] Furthermore, the alcohol-soluble thermosetting resin includes one or more of phenolic, epoxy, and vinyl ester.

[0017] Furthermore, in step 4), the furnace chamber pressure in the sintering furnace is maintained at a positive pressure of 20-50 KPa, and the temperature is increased to 800° C. at a rate of 10-30° C. / min and kept at this temperature for 30-90 minutes.

[0018] Furthermore, in step 5), the operating parameters of the sintering furnace during the carbonization treatment are to increase the temperature to 1200-1500° C. at 10° C. / min for carbonization and keep the temperature for 30-60 minutes.

[0019] Furthermore, in step 5), during the graphitization treatment, the operating parameters of the sintering furnace are to increase the temperature to 1800-2000° C. at 5° C. / min and keep the temperature for 20-40 minutes.

[0020] Further, step 6) comprises:

[0021] Performing liquid phase activation treatment in a strong acid at a predetermined temperature;

[0022] The activated samples were placed in anhydrous ethanol for ultrasonic cleaning;

[0023] The ultrasonically cleaned sample is placed in a heated electrolytic bath for electroplating;

[0024] The electroplated sample is washed with deionized water and dried to obtain metal-modified carbon paper for fuel cells.

[0025] Furthermore, the predetermined temperature in step 6) is 30-60°C.

[0026] Furthermore, the strong acid in step 6) is hydrochloric acid, sulfuric acid or nitric acid.

[0027] Furthermore, in step 6), the electroplating solution in the electrolytic cell includes 200-240 g / L of nickel sulfate, 20-40 g / L of nickel chloride, 70-90 g / L of sodium citrate and 20-50 g / L of boric acid.

[0028] A second aspect of the present invention provides a metal-modified carbon paper for a fuel cell, which is produced by the above-mentioned production method.

[0029] A third aspect of the present invention provides a fuel cell, comprising the above-mentioned metal-modified carbon paper for fuel cells.

[0030] The present invention performs impregnation and doping of titanium hydride powder and heat pressing on a carbon paper precursor to decompose titanium hydride into metallic titanium and hydrogen. The escape of hydrogen forms micropores in the resin that wraps the hydride powder, thereby improving the air permeability of the carbon paper. The metallic titanium reacts chemically with carbon element at high temperature to generate carbide, thereby improving the bonding strength with carbon fiber and improving the conductivity.

[0031] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : The morphology of carbon paper after graphitization in Example 1 of the present invention;

[0033] Figure 2 : Morphology of carbon paper after graphitization and nickel electroplating in Example 1;

[0034] Figure 3 : The morphology of carbon paper after graphitization in Comparative Example 4;

[0035] Figure 4 : The carbon paper morphology of graphitized carbon paper in Comparative Example 6;

[0036] Figure 5 : Plane resistance and sheet resistivity in all embodiments and comparative examples;

[0037] Figure 6 : Gas flow rate in all embodiments and comparative examples;

[0038] Figure 7 : Tensile stress-strain curves in all Examples and Comparative Examples. DETAILED DESCRIPTION

[0039] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that the present invention will be more comprehensive and complete and fully convey the concept of the example embodiments to those skilled in the art.

[0040] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0041] A first aspect of the present invention provides a method for manufacturing carbon paper for a metal-modified fuel cell, comprising the following steps:

[0042] 1) impregnating a carbon paper precursor in an impregnation solution to which titanium hydride powder is added; wherein the carbon paper precursor is a carbon fiber fabric such as carbon felt or carbon cloth; the titanium hydride powder has a purity of 99.9% or more and is an ultrafine powder with a particle size of less than 10 microns;

[0043] 2) drying the impregnated carbon paper precursor;

[0044] 3) The dried carbon paper precursor is clamped between the graphite sheets and placed in a sintering furnace for gas hot pressing;

[0045] 4) After the gas hot pressing is completed, the furnace chamber gas is released, and the sintering furnace is heated to a predetermined temperature at a predetermined heating rate under a positive pressure environment, so that the titanium hydride is completely decomposed into titanium and hydrogen;

[0046] 5) After step 4), carbonization and graphitization are sequentially performed in a sintering furnace.

[0047] In one embodiment of the present invention, step 5) further includes the following steps:

[0048] 6) The graphitized sample after step 5) is subjected to nickel plating to obtain metal-modified carbon paper for fuel cells.

[0049] In one embodiment of the present invention, the amount of titanium hydride powder added in step 1) accounts for 1-10 wt.% of the mass of the impregnation solution.

[0050] In one embodiment of the present invention, the impregnation liquid includes 50-75% of anhydrous ethanol and 25-50% of alcohol-soluble thermosetting resin in weight percentage.

[0051] In one embodiment of the present invention, the alcohol-soluble thermosetting resin includes one or more of phenolic, epoxy, and vinyl ester.

[0052] In one embodiment of the present invention, in step 4), the furnace chamber pressure in the sintering furnace is maintained at a positive pressure of 20-50 KPa, and the temperature is increased to 800° C. at a rate of 10-30° C. / min and kept at this temperature for 30-90 minutes.

[0053] In one embodiment of the present invention, during the carbonization treatment in step 5), the operating parameters of the sintering furnace are to increase the temperature to 1200-1500° C. at 10° C. / min for carbonization and keep the temperature for 30-60 minutes.

[0054] In one embodiment of the present invention, during the graphitization treatment in step 5), the operating parameters of the sintering furnace are to increase the temperature to 1800-2000° C. at 5° C. / min and keep the temperature for 20-40 minutes.

[0055] In one embodiment of the present invention, step 6) includes:

[0056] Performing liquid phase activation treatment in a strong acid at a predetermined temperature;

[0057] The activated samples were placed in anhydrous ethanol for ultrasonic cleaning;

[0058] The ultrasonically cleaned sample is placed in a heated electrolytic bath for electroplating;

[0059] The electroplated sample is washed with deionized water and dried to obtain metal-modified carbon paper for fuel cells.

[0060] In one embodiment of the present invention, the predetermined temperature in step 6) is 30-60°C.

[0061] In one embodiment of the present invention, the strong acid in step 6) is hydrochloric acid, sulfuric acid or nitric acid.

[0062] In one embodiment of the present invention, the electroplating solution in the electrolytic cell in step 6) includes 200-240 g / L of nickel sulfate, 20-40 g / L of nickel chloride, 70-90 g / L of sodium citrate and 20-50 g / L of boric acid. The introduction of sodium citrate into the electroplating solution can well adjust the pH value of the electroplating solution, and sodium citrate is environmentally friendly and pollution-free, and has low corrosiveness.

[0063] A second aspect of the present invention provides a metal-modified carbon paper for a fuel cell, which is produced by the above-mentioned production method.

[0064] A third aspect of the present invention provides a fuel cell, comprising the above-mentioned metal-modified carbon paper for fuel cells.

[0065] In order to enable those skilled in the art to more clearly understand the method for manufacturing the metal-modified fuel cell carbon paper of the present invention, several specific embodiments are listed to specifically introduce the method for manufacturing the carbon paper as follows:

[0066] Embodiment 1:

[0067] Step 1) Impregnation: Take an impregnation solution with a weight fraction ratio of 75% anhydrous ethanol and 25% alcohol-soluble thermosetting resin, and add 1wt.% of titanium hydride powder to it. Add a magnetic stirrer rotor, stir it magnetically to make it fully mixed, and finally add the carbon paper precursor for impregnation, and impregnate for 10 minutes.

[0068] Step 2) Drying: Place the impregnated carbon paper precursor in an oven at 100° C. and dry for 10 minutes.

[0069] Step 3) Gas hot pressing: Place the dried sample in step 2) between two smooth graphite plates and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber and evacuate the chamber until the vacuum degree is less than 10 -2 pa, and then fill with high-purity protective gas (≥99.99%), so that the test furnace chamber reaches 3MPa, then start the temperature increase program, increase to 180℃ at 40℃ / min, and keep warm for 1 minute for gas hot pressing.

[0070] Step 4) After the body hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slightly positive pressure of 20 KPa. At the same time, the temperature is raised to 800° C. at 20° C. / min and kept at this temperature for 60 minutes to decompose the hydride into metallic titanium and hydrogen.

[0071] Step 5) The temperature is then raised to 1200°C at 10°C / min for carbonization and kept at this temperature for 30 minutes. Finally, the temperature is raised to 2000°C at 5°C / min and kept at this temperature for 20 minutes for graphitization. The sample is removed after the high temperature furnace cools to room temperature.

[0072] Step 6) Electroplating: The sample after graphitization in step 5) is first subjected to liquid phase activation treatment in nitric acid at 60°C for 30 minutes, then ultrasonically cleaned in anhydrous ethanol, washed and blown dry. It is placed in an electroplating tank as an electroplating cathode material, and pure nickel is used as an anode material. Then, 240g / L of nickel sulfate, 20g / L of nickel chloride, 70g / L of sodium citrate and 20g / L of boric acid are added to the heated electroplating tank to cover the anode and cathode materials, and then the power supply is turned on to maintain a voltage of 10V for electroplating after the temperature is raised to 50°C. After electroplating, it is washed with deionized water and blown dry to obtain a modified carbon paper for fuel cells.

[0073] A metal-modified proton exchange membrane fuel cell carbon paper with a thickness of 0.18 mm was obtained. Figure 5 , 6 The air permeability is 3641 mL·mm / cm 2 ·h·mmHg, tensile strength 78.3MPa, plane resistivity 3.2mΩ·cm. Figure 1 It was found that when the graphitization temperature was lowered, a carbon paper with uniform pore distribution was formed, and a small amount of titanium particles adhered to the carbon fibers, indicating that the titanium particles have a catalytic graphitization effect. Figure 2 In the process, the electroplated nickel layer wraps the carbon fiber and resin carbon well, thereby greatly reducing the resistivity of the carbon paper.

[0074] Embodiment 2:

[0075] Step 1) Impregnation: Take 50% anhydrous ethanol and 50% alcohol-soluble thermosetting resin in a weight fraction ratio to prepare an impregnation solution, and add 10wt.% of titanium hydride powder to the impregnation solution. Add a magnetic stirrer rotor, stir magnetically to mix thoroughly, and finally add the carbon paper precursor for impregnation for 10 minutes.

[0076] Step 2) Drying: Place the impregnated carbon paper precursor in an oven at 100° C. and dry for 10 minutes.

[0077] Step 3) Gas hot pressing: Place the dried sample in step 2) between two smooth graphite plates and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber and evacuate the chamber until the vacuum degree is less than 10 -2 pa, and then fill with high-purity protective gas (≥99.99%), so that the test furnace chamber reaches 1MPa, then start the temperature increase program, increase to 170℃ at 40℃ / min, and keep warm for 2 minutes for gas hot pressing.

[0078] Step 4) After the gas hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slightly positive pressure of 20 KPa. At the same time, the temperature is raised to 800° C. at 20° C. / min and kept at this temperature for 60 minutes to decompose the hydride into metallic titanium and hydrogen.

[0079] Step 5) The temperature is then raised to 1400°C at 10°C / min for carbonization and kept at this temperature for 30 minutes. Finally, the temperature is raised to 1800°C at 5°C / min and kept at this temperature for 20 minutes for graphitization. The sample is removed after the high temperature furnace cools to room temperature.

[0080] Step 6) Electroplating: The sample after graphitization in step 5) is first subjected to liquid phase activation treatment in nitric acid at 60°C for 30 minutes, then ultrasonically cleaned in anhydrous ethanol, and then blown dry. It is placed in an electroplating tank as an electroplating cathode material, and pure nickel is used as an anode material. Then, 220g / L of nickel sulfate, 30g / L of nickel chloride, 80g / L of sodium citrate, and 30g / L of boric acid are added to the heated electroplating tank to cover the anode and cathode materials, and then the temperature is raised to 60°C and the power supply is turned on to maintain a voltage of 10V for electroplating. After electroplating, it is washed with deionized water and blown dry to obtain a modified carbon paper for fuel cells.

[0081] A metal-modified proton exchange membrane fuel cell carbon paper with a thickness of 0.2 mm was obtained. Figure 5 , 6 And 7 its air permeability 4340mL·mm / cm 2 ·h·mmHg, tensile strength 85.1MPa, plane resistivity 3.3mΩ·cm.

[0082] Embodiment 3:

[0083] Step 1) Impregnation: Take an impregnation solution with a weight fraction ratio of 90% anhydrous ethanol and 10% alcohol-soluble thermosetting resin, and add 5wt.% of titanium hydride powder to it. Add a magnetic stirrer rotor, stir it magnetically to make it fully mixed, and finally add the carbon paper precursor for impregnation, and impregnate for 10 minutes.

[0084] Step 2) Drying: Place the impregnated carbon paper precursor in an oven at 100° C. and dry for 10 minutes.

[0085] Step 3) Gas hot pressing: Place the dried sample in step 2) between two smooth graphite plates and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber and evacuate the chamber until the vacuum degree is less than 10 -2 pa, and then fill with high-purity protective gas (≥99.99%), so that the test furnace chamber reaches 5MPa, then start the temperature increase program, increase to 160℃ at 40℃ / min, and keep warm for 1 minute for gas hot pressing.

[0086] Step 4) After the gas hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slightly positive pressure of 20 KPa. At the same time, the temperature is raised to 800° C. at 20° C. / min and kept at this temperature for 60 minutes to decompose the hydride into metallic titanium and hydrogen.

[0087] Step 5) The temperature is then raised to 1400°C at 10°C / min for carbonization and kept at this temperature for 30 minutes. Finally, the temperature is raised to 1900°C at 5°C / min and kept at this temperature for 30 minutes for graphitization. The sample is removed after the high temperature furnace cools to room temperature.

[0088] Step 6) Electroplating: The sample after graphitization in step 5) is first subjected to liquid phase activation treatment in nitric acid at 60°C for 30 minutes, then ultrasonically cleaned in anhydrous ethanol, and then blown dry. It is placed in an electroplating tank as an electroplating cathode material, and pure nickel is used as an anode material. Then, 240g / L of nickel sulfate, 40g / L of nickel chloride, 80g / L of sodium citrate, and 40g / L of boric acid are added to the heated electroplating tank to cover the anode and cathode materials, and then the power supply is turned on to maintain a voltage of 10V for electroplating after the temperature is raised to 60°C. After electroplating, it is washed with ionized water and blown dry to obtain a modified carbon paper for fuel cells.

[0089] A metal-modified proton exchange membrane fuel cell carbon paper with a thickness of 0.2 mm was obtained. Figure 5 , 6 And 7 its air permeability is 3869mL·mm / cm 2 ·h·mmHg, tensile strength 77.5MPa, plane resistivity 3.1mΩ·cm.

[0090] Comparative Example 4:

[0091] Step 1) Impregnation: Take 50% anhydrous ethanol and 50% alcohol-soluble thermosetting resin in a weight fraction ratio to prepare an impregnation solution, and add 5wt.% of titanium hydride powder to the impregnation solution. Add a magnetic stirrer rotor, stir magnetically to mix thoroughly, and finally add the carbon paper precursor for impregnation for 10 minutes.

[0092] Step 2) Drying: Place the impregnated carbon paper precursor in an oven at 100° C. and dry for 10 minutes.

[0093] Step 3) Gas hot pressing: Place the dried sample in step 2) between two smooth graphite plates, and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber, evacuate the chamber to a vacuum level lower than 10-2pa, and then fill it with high-purity protective gas (≥99.99%) until the chamber reaches 1MPa, then start the heating program, raise the temperature to 170°C at 40°C / min, and keep it warm for 2 minutes for gas hot pressing.

[0094] Step 4) After the gas hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slightly positive pressure of 20 KPa. At the same time, the temperature is increased to 800°C at 20°C / min and kept at this temperature for 60 minutes to decompose the hydride into metal and hydrogen.

[0095] Step 5) The temperature is then raised to 1400°C at 10°C / min for carbonization and kept at this temperature for 30 minutes. Finally, the temperature is raised to 1800°C at 5°C / min and kept at this temperature for 20 minutes for graphitization. The sample is removed after the high temperature furnace cools to room temperature.

[0096] A 0.2 mm thick titanium hydride modified proton exchange membrane fuel cell carbon paper was obtained. Figure 5 , 6 The air permeability is 2948 mL·mm / cm 2 ·h·mmHg, tensile strength 44.7MPa, plane resistivity 6.2mΩ.cm. In addition, Figure 3 It can be seen that the titanium particles are evenly dispersed on the carbon fibers, which can effectively improve the conductivity of the carbon paper. Compared with the above examples 1-3, the nickel plating process of step 6) is not performed after step 5), and the mechanical strength of the carbon paper prepared in the above examples is lower.

[0097] Comparative Example 5:

[0098] Impregnation: Take 50% anhydrous ethanol and 50% alcohol-soluble thermosetting resin in a weight fraction ratio to prepare an impregnation solution, add a magnetic stirrer rotor, stir magnetically to mix it thoroughly, and finally add the carbon paper precursor for impregnation for 10 minutes.

[0099] Drying: Place the impregnated carbon paper precursor in an oven at 100°C and dry for 10 minutes.

[0100] Sintering: Place the dried sample in step 2 between two smooth graphite plates and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber and evacuate the chamber until the vacuum degree is less than 10- 2 pa, and then fill with high-purity protective gas (≥99.99%), so that the test furnace chamber reaches 1MPa, then start the temperature increase program, increase to 170℃ at 40℃ / min, and keep warm for 2 minutes for gas hot pressing.

[0101] After the gas hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slight positive pressure of 20KPa.

[0102] The temperature was then raised to 1400°C at a rate of 10°C / min and maintained at that temperature for 30 minutes for carbonization.

[0103] Finally, the temperature was raised to 2400°C at 5°C / min and kept at that temperature for 30 minutes for graphitization. The sample was taken out after the high temperature furnace cooled to room temperature.

[0104] Electroplating: The sample after graphitization in step 3 is first subjected to liquid phase activation treatment in nitric acid at 60°C for 30 minutes, then ultrasonically cleaned in anhydrous ethanol, washed and blown dry. It is placed in an electroplating tank as an electroplating cathode material, and pure nickel is used as an anode material. Then, 240g / L of nickel sulfate, 40g / L of nickel chloride, 80g / L of sodium citrate and 40g / L of boric acid are added to the heated electroplating tank to cover the anode and cathode materials, and then the power supply is turned on to maintain a voltage of 10V for electroplating after the temperature is raised to 60°C. After electroplating, it is washed in deionized water and blown dry to obtain a modified carbon paper for fuel cells.

[0105] A metal-modified proton exchange membrane fuel cell carbon paper with a thickness of 0.2 mm was obtained. Figure 5 , 6 The air permeability is 2346 mL·mm / cm 2 ·h·mmHg, tensile strength 43.9MPa, plane resistivity 3.9mΩ·cm. In this comparative example, titanium hydride powder was not added to the impregnation solution, and the air permeability and conductivity of the carbon paper were reduced.

[0106] Comparative Example 6:

[0107] Impregnation: Take 50% anhydrous ethanol and 50% alcohol-soluble thermosetting resin in a weight fraction ratio to prepare an impregnation solution, add a magnetic stirrer rotor, stir magnetically to mix it thoroughly, and finally add the carbon paper precursor for impregnation for 10 minutes.

[0108] Drying: Place the impregnated carbon paper precursor in an oven at 100°C and dry for 10 minutes.

[0109] Sintering: Place the dried sample in step 2 between two smooth graphite plates, and then place it in the furnace chamber of a high-temperature gas pressure sintering furnace. Close the furnace chamber, evacuate the chamber to a vacuum level lower than 10-2pa, and then fill it with high-purity protective gas (≥99.99%) until the chamber reaches 1MPa, then start the heating program, raise the temperature to 170°C at 40°C / min, keep the temperature for 2 minutes, and perform gas hot pressing.

[0110] After the gas hot pressing is completed, the furnace chamber gas is released to keep the furnace chamber pressure at a slight positive pressure of 20KPa.

[0111] The temperature was then raised to 1400°C at a rate of 10°C / min and maintained at that temperature for 30 minutes for carbonization.

[0112] Finally, the temperature was raised to 2400°C at 5°C / min and kept at that temperature for 30 minutes for graphitization. The sample was taken out after the high temperature furnace cooled to room temperature.

[0113] A carbon paper for proton exchange membrane fuel cells with a thickness of 0.22 mm was obtained from Figure 5 ,6 and 7, its air permeability is 2022mL·mm / cm2·h·mmHg, tensile strength is 35.1MPa, and plane resistivity is 7.3mΩ·cm. In addition, according to Figure 4 It was found that when the graphitization temperature was too high, a large amount of resin carbon flakes were formed, resulting in a decrease in the air permeability of the carbon paper.

[0114] In summary, through the comparison results of the above embodiments and comparative examples, it can be seen that the technical solution of the present application has the following beneficial technical effects:

[0115] 1) The present application performs an impregnation doping treatment on the carbon paper precursor with titanium hydride powder. Compared with adding pure metal, titanium hydride powder will decompose into metallic titanium and hydrogen at 800°C. The escape of hydrogen will form micropores in the resin that wraps the hydride powder, thereby improving the air permeability of the carbon paper. Compared with adding pure copper powder, the titanium formed by the decomposition of titanium hydride powder will react chemically with carbon element at high temperature to form carbide, which improves the bonding strength with carbon fiber.

[0116] 2. Compared with the traditional process of hot pressing, carbonization and graphitization in steps, this application adopts an integrated sintering preparation process, using a high-temperature gas pressure sintering furnace to replace the hot press, carbonization furnace and graphitization furnace, saving equipment costs and simplifying the preparation process; in the gas hot pressing stage, the smooth graphite plate acts as the hot pressing plate of the hot press; finally, the furnace cavity is kept slightly positive, so that the carbon paper in the graphite plate interlayer will not curl due to uneven stress distribution, thereby improving the product yield. By using gas pressurization, all carbon papers can be hot pressed at the same time, keeping the pressure in all directions equal, ensuring the consistency of the product, and it is a mass production.

[0117] 3. The presence of hydride powder in this application can effectively reduce the graphitization transition temperature of the resin. Since the titanium decomposed by titanium hydride is a carbide-forming element, part of it will replace the carbon atoms in the hexagonal carbon lattice to form a solid solution, and part of it will react with carbon. The mechanism is dissolution and precipitation (it can also be called catalytic graphitization), thereby greatly reducing the graphitization temperature and saving energy. In addition, metallic titanium will also reduce the resistivity of carbon paper, thereby improving conductivity.

[0118] 4. After graphitization, carbon paper will become hard and brittle, and its mechanical properties are poor. The surface modification using nickel plating in this application will not only improve the mechanical properties, greatly improve the rigidity and tensile strength of carbon paper, but also improve the conductivity of carbon paper. In addition, the introduction of sodium citrate into the traditional electroplating solution can well adjust the pH value of the electroplating solution, and sodium citrate is environmentally friendly and pollution-free, and has low corrosiveness. It should be noted that the above embodiments listed in the present invention are only illustrative, and the present invention is not limited thereto.

[0119] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.

[0120] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for producing carbon paper for metal-modified fuel cells, characterized in that: The steps include: 1) impregnating a carbon paper precursor in an impregnation solution containing titanium hydride powder; 2) drying the impregnated carbon paper precursor; 3) The dried carbon paper precursor is clamped between the graphite sheets and placed in a sintering furnace for gas hot pressing; 4) After the gas hot pressing is completed, the furnace chamber gas is released, and the sintering furnace is heated to a predetermined temperature at a predetermined heating rate under a positive pressure environment, so that the titanium hydride is completely decomposed into titanium and hydrogen; 5) After step 4), carbonization and graphitization are sequentially performed in a sintering furnace.

2. The manufacturing method according to claim 1, characterized in that Step 5) also includes the following steps: 6) The graphitized sample after step 5) is subjected to nickel plating to obtain metal-modified carbon paper for fuel cells.

3. The manufacturing method according to claim 1, characterized in that: In step 1), the amount of titanium hydride powder added is 1-10 wt.% of the mass of the impregnation solution.

4. The manufacturing method according to claim 1, characterized in that: The impregnation liquid comprises 50-75% of anhydrous ethanol and 25-50% of alcohol-soluble thermosetting resin in terms of weight percentage.

5. The manufacturing method according to claim 3, characterized in that: The alcohol-soluble thermosetting resin includes one or more of phenolic, epoxy, and vinyl ester.

6. The manufacturing method according to claim 1, characterized in that: In step 4), the pressure of the furnace chamber in the sintering furnace is maintained at a positive pressure of 20-50 KPa, and the temperature is increased to 800° C. at a rate of 10-30° C. / min and kept at this temperature for 30-90 minutes.

7. The manufacturing method according to claim 1, characterized in that: In step 5), the sintering furnace operating parameters for carbonization treatment are to increase the temperature to 1200-1500° C. at 10° C. / min for carbonization and keep the temperature for 30-60 minutes.

8. The manufacturing method according to claim 1, characterized in that: In step 5), during the graphitization treatment, the operating parameters of the sintering furnace are to increase the temperature to 1800-2000° C. at 5° C. / min and keep the temperature for 20-40 minutes.

9. The manufacturing method according to claim 2, characterized in that: Step 6) includes: Performing liquid phase activation treatment in a strong acid at a predetermined temperature; The activated samples were placed in anhydrous ethanol for ultrasonic cleaning; The ultrasonically cleaned sample is placed in a heated electrolytic bath for electroplating; The electroplated sample is washed with deionized water and dried to obtain metal-modified carbon paper for fuel cells.

10. A metal-modified carbon paper for a fuel cell, characterized in that: The invention is prepared by the manufacturing method according to any one of claims 1 to 9.

11. A fuel cell, characterized in that: The invention comprises the metal-modified carbon paper for fuel cells as claimed in claim 10.

Citation Information

Patent Citations

  • Carbon fiber paper and porous carbon electrode substratefor fuel cell therefrom

    CN100336972C

  • Gas diffusion layer material for fuel cell and preparation method thereof

    CN1331261C

  • Titanium material or titanium alloy material that have surface conductivity, fuel cell separator using same, and fuel cell

    CN105934842A

  • Preparation method of high-permeability carbon paper for fuel cell

    CN114361482A

  • Improvements in fuel cells for the generation of electrical energy

    GB1022690A